Promising Configurations for Future Passenger Aircraft - Dieter Scholz (Springer, 2017)
A promising aircraft configuration for typical short to medium range would be a turboprop aircraft with large propeller diameter. The concept can benefit further from a strut braced wing and natural laminar flow. Most important for an efficient aircraft design is a high aspect ratio. For a given span (limits at airports need to be observed) the effective aspect ratio can be increased with winglets or folding wings. Much better would be to offer wing tip extensions to standard aircraft, accepting the next larger ICAO wing span category for some aircraft in the fleet. Electric flight on batteries is not the answer due to severe range limitations. Regenerative energy could be converted to hydrogen with electrolysis and stored as liquid hydrogen (LH2) in a stretched fuselage with hydrogen tanks installed in front and aft of the cabin. Research is on the way to directly convert (regenerative electrical) energy to hydrocarbons. Such synthetic fuel could be used even in older aircraft offering a fast improvement for the environment.
Keywords: Passenger aircraft; Payload; Cargo; Hydrogen tank; Synthetic fuel; Drop-in fuel; Turboprop; Braced wing; Natural laminar flow; High aspect ratio; Span; Battery; Hydrogen; Stretch; Synthetic fue